18‐Sided polygon voltage space vector fed nine‐phase induction machine drive for high power applications. (28th September 2021) - Vemula, Janaki Ramaiah; Keerthipati, Sivakumar
Abstract: The advantages such as better fault‐tolerant capability, less space harmonic content, and requirement of power semiconductor devices with reduced voltage ratings etc., made the multi‐phase induction machines drives (IMD) best desirable for the high power applications. However, as the number of phase increases, the improvement in the LMR of the multi‐phase IMDs is not significant using the conventional SVPWM techniques provided in the literature. To address the above‐mentioned limitation, 18‐sided polygon (octadecagon) based voltage space vector generation for a nine‐phase IMD is proposed in this article without compromising in the torque harmonic profile. Using the proposed octadecagonal voltage space vector generation technique, the LMR of nine‐phase IMD is significantly improved by 26.03%, 24.28%, and 9.15% in comparison to the nine‐phase sinusoidal pulse width modulation, nine‐phase SVPWM and individual hexagonal SVPWM techniques, respectively. Efficacy of the proposed control technique is substantiated using the results obtained from ANSYS Maxwell simulation and experimentation on 5‐hp nine‐phase IMD prototype in the laboratory. Abstract : This article presents an 18‐sided polygon (octadecagon) based voltage space vector generation for nine‐phase induction machine drives (IMD), which are mostly preferred for high‐power applications, to improve the linear modulation region compared to the conventional techniques. In addition, neutrals are isolated to eliminate the flow of triplen harmonic currents through the phase windings of nine‐phase IMD.